Obstetric outcomes of teenage pregnancies: A record-based study in a rural hospital of North 24 Parganas district, West Bengal - Paramita Sarkar; Payel Sarkar; Arnab Sarkar; Saibendu Kumar Lahiri (Asian Journal of Medical Sciences, 2024)
Background: Teenage pregnancy is a pregnancy in a woman within 10–19 years of age groups. It results from a number of factors such as early age at marriage, illiteracy, poverty, premarital sex, lack of awareness, and access to contraception. Teenage pregnancy imposes serious social and medical implications relating to both maternal and child health. It is a worldwide public health problem in both developed and developing countries.